The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/app.48581
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Young's modulus for polypropylene: Influence of initial crystallinity and service temperature

Abstract: In this study, the mechanical properties of isotactic polypropylene (iPP) materials with different crystallinities at room and elevated temperatures were investigated. In order to obtain samples with a certain range of crystallinity, and to ensure a uniform microstructure of these samples, the iPP samples obtained by injection molding required melt compression molding and controlled annealing. In the macromechanical studies, the experimental results showed that the storage modulus and Young's modulus of polypr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 44 publications
6
20
0
Order By: Relevance
“…It has been shown that the degree of crystallinity is linked to the Young's modulus. [ 28,53 ] As shown in Figure S3, the maximum level of both responses was achieved at 30 mm/s. This could be related to the fact that this speed gives enough time to PPS chains to organize into crystalline regions, resulting in a high elastic behavior of the parts.…”
Section: Resultsmentioning
confidence: 94%
“…It has been shown that the degree of crystallinity is linked to the Young's modulus. [ 28,53 ] As shown in Figure S3, the maximum level of both responses was achieved at 30 mm/s. This could be related to the fact that this speed gives enough time to PPS chains to organize into crystalline regions, resulting in a high elastic behavior of the parts.…”
Section: Resultsmentioning
confidence: 94%
“…The crystallinities of each layer in the model were obtained by measuring the corresponding positions of molded parts with WAXD. The mechanical properties of each layer necessary for prediction were calculated using the following model describing the elastic modulus with the influence of temperature and crystallinity [ 24 ]. where θ 0 is the reference temperature (room temperature); E 0 is the elastic modulus at the reference temperature; a , b , and c are material parameters; w and θ are the crystallinity and service temperature, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The thicknesses of the multi-layers were determined as the thicknesses of the skin-core structure in the molded parts, measured using a polarizing microscope (PLM). A model was introduced to describe the elastic modulus with the influence of temperature and crystallinity [ 24 ]. Finally, the predicted results were compared with the warpage information of the parts obtained using a 3D laser scanner.…”
Section: Introductionmentioning
confidence: 99%
“…In Thomason et al's study, the test is performed from 233 K. However, the matrix Young's modulus below room temperature used in the model predictions is not obtained. Li et al [52] provided the Young's modulus of PP with different crystallinity values above room temperature. We use these values to predict the ISS at elevated temperature, respectively, and then the average values are taken.…”
Section: Fiber Agglomerationmentioning
confidence: 99%